Capacity building to bridge data use and instructional improvement through evidence on student thinking. (June 2021) - Datnow, Amanda; Lockton, Marie; Weddle, Hayley
Highlights: Evidence from student thinking can be a useful form of data to guide instruction. Knowing how to draw on student thinking requires teacher capacity building. Learning how to use data as part of instruction supported teacher reflection. Abstract: While schools and systems across the globe promote data-driven decision making, teachers often struggle to use data, especially from external assessments, to inform daily instruction. In this paper, we examine teacher capacity building for a less typical form of data use - evidence on student thinking. We draw on data from a longitudinal, in-depth qualitative study involving middle school math teachers who were engaged in an instructional improvement project. Findings show that data use occurred when evidence from student thinking was introduced as part of the instructional planning process. This shift was facilitated by an instructional coach whose capacity building efforts with teachers focused on coherence, specifically planning high quality instruction and using data effectively, while also meeting district pacing and unit planning goals. When teachers put new strategies into practice, feedback from formative assessment data allowed teachers to identify and address misconceptions in student thinking. Learning how to use data as part of instruction helped teachers build capacity to reflect on their own practice. Implications for theory, practice, and research are discussed.